Iliac vein perforation caused by dialysis catheterisation: a case report - Zheng, Peng; Wang, Xiaoqian (Journal of the Pakistan Medical Association, 2025)
In the context of haemodialysis for patients with end-stage renal failure, central venous catheterisation is often required to establish a vascular access route. However, procedural complications, including acute vascular rupture and haemorrhage may occur. Although rare, these complications pose significant management challenges, high treatment costs and substantial patient trauma, with some cases progressing to life-threatening emergencies. Notably, there are no previously reported cases of iliac vein perforation secondary to haemodialysis catheterisation. We present a case of right common iliac vein (CIV) perforation by a haemodialysis catheter extending into the psoas muscle, resulting in a massive retroperitoneal haematoma and haemorrhagic shock (HS). Keywords: Chronic kidney disease, Haemodialysis, Internal jugular vein, Central venous stenosis.